Beyond the "grid-lock" in electricity interconnectors: The case of Germany and Poland - Lidia Puka; Kacper Szulecki (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The common European electricity market requires both market integration and transmission grid expansion, including trans-border interconnectors. Although the benefits of increased interconnectivity are widely acknowledged, expansion of interconnectors is often very slow. This paper gathers insights on the reasons behind this grid-lock drawing on the study of the German-Polish border. Although two interconnectors already exist, the trade is blocked by unplanned electricity loop flows. A third interconnector has been discussed for years, but saw little progress in spite of declarations of support on both sides. Drawing on the existing literature on the topic of grid expansion we identify four hypotheses for the grid-lock: inadequate financing; diverging interests; governance and administration problems; and different actors' motivations, trust and security perceptions. We evaluate them using the empirical material gathered through document analysis and stakeholder interviews conducted in Germany and Poland. None of the hypotheses on its own can explain the gridlock. However, while financing has not been a major obstacle, divergent interests had an impact on the project delay, administrative and governance problems are a great hindrance on the technical level, while motivations influence interstate political relations and policy shaping. EU support and closer bilateral cooperation provide opportunities to address these challenges.
Keywords: N7; N74; Q4; Q48; 330; electricity interconnectors; the European Union; loop-flows